Isoflurane Postconditioning Alleviates Ischemic Neuronal Injury Via MiR-384-5p Regulated Autophagy. (1st May 2023) - Zhu, Xin; Yang, Mei; Yang, Liu
Highlights: Isoflurane postconditioning alleviates ischemic neuronal injury. MiR-384-5p targets ATG5 to inhibit autophagy. MiR-384-5p inhibitors could reverse the neuroprotective effect of isoflurane in MCAO rats. Abstract: The purpose of the study was to investigate the effect of isoflurane postconditioning on neuron injury in MCAO (middle cerebral artery occlusion) rats and its molecular mechanism of affecting autophagy through miR-384-5p/ATG5 (autophagy-related protein 5). HT22 cells (mouse hippocampal neuronal cell line) were exposed to 1.5% isoflurane for 30 min after OGD/R (oxygen–glucose deprivation/reoxygenation). Flow cytometry and CCK-8 kit were used to analyze changes in apoptosis and cell viability. The level of miR-384-5p was detected by qRT-PCR. Targetscan database prediction combined with dual luciferase reporter gene assay confirmed ATG5 as a target molecule downstream of miR-384-5p. In addition, western blot results confirmed that isoflurane postconditioning regulated miR-384-5p/ATG5 and significantly inhibited the expression of apoptosis-related proteins. Meanwhile, immunofluorescence staining for LC3II positivity combined with western blot results revealed that isoflurane postconditioning significantly inhibited autophagy. In vivo, MCAO induced neuronal injury for 90 min, followed by 24-h reperfusion. Isoflurane postconditioning (Iso) group underwent 1.5% isoflurane postconditioning for 60 min after reperfusion. Neurological scoring and TTC staining were used to evaluate the protective effect of isoflurane post-treatment on neurological injury, respectively. TUNEL staining and western blot results confirmed that isoflurane post-conditioning could regulate miR-384-5p and inhibit apoptosis. Immunofluorescence staining and western blot results confirmed that isoflurane post-conditioning inhibited autophagy in MCAO rats. Based on the above results, we speculated that the molecular mechanism of isoflurane post-conditioning to alleviate ischemic neuronal injury may be related to the regulation of miR-384-5p/ATG5-mediated autophagy.